Association between TLR4 and TLR9 Gene Polymorphisms with Development of Pulmonary Tuberculosis in Zahedan, Southeastern Iran - Danial Jahantigh; Saeedeh Salimi; Roya Alavi-Naini; Abolfazl Emamdadi; Hamid Owaysee Osquee; Farzaneh Farajian Mashhadi (The Scientific World Journal)
Some evidence suggests that a variety of genetic factors contribute to development of the tuberculosis (TB). TLR4 and TLR9 have been proposed as susceptibility genes for TB. This study was performed in 124 newly diagnosed TB cases and 149 healthy controls in a TB-endemic region of Iran. The TLR4 genes Asp299Gly, Thr399Ile, and TLR9 gene T-1486C polymorphisms were amplified by polymerase chain reaction (PCR) and then detected by PCR-restriction fragment length polymorphism (RFLP). The frequencies of the mutant alleles of TLR4 Arg299Gly, Thr399Ile, and TLR9 T-1486C polymorphisms were 0.8 versus 0.1, 5.6 versus 3, and 28.6 versus 25.2 in patients and controls, respectively, that were not significant. The synergic effect of TI,II/CC genotypes for TLR4 Thr399Ile and TLR9 T-1486C polymorphisms showed increased risk of PTB susceptibility. In conclusion, no significant relation was found between TLR4 and TLR9 polymorphisms alone and PTB. However, synergic effects of TLR4 Thr399Ile and TLR9-1486T/C polymorphisms might increase risk of PTB.